Role of MoS2 morphology on wear and friction under spectrum loading conditions. (21st April 2015) - Bagi, Sujay D.; Aswath, Pranesh B.
Abstract One of the ways by which grease is evaluated is by using a four‐ball wear test using ASTM D2266. However, actual applications may require bearings to be subjected to spectrum loading conditions. This study focuses on using ball milling to mitigate the wear from sharp edges in the MoS2 particles. Two different blends of greases were formulated using MoS2 in the as‐received state (unmilled) and milled MoS2; they were tested under spectrum loading conditions where the load and frequency of the tests were treated as variables. It was found that ball milling of the MoS2 significantly reduces the wear under spectrum loading condition both for ramp‐up and ramp‐down conditions. It was also shown that shortening the time step for both the ramp‐up and ramp‐down cycles resulted in larger wear for unmilled MoS2 particles in comparison with milled MoS2 particles in grease. The milling process did not play a significant role when frequency of the test was either ramped up or down. Copyright © 2015 John Wiley & Sons, Ltd.